The role of B cell receptor clone test and Adiponectin as a predictors of rheumatoid arthritis - Krakhei, Afrah Shlba; Al-Gebori, Abdulnasser M; Alosami, Mohammed Hadi Munshed (International Journal of Psychosocial Rehabilitation, 2020)
Rheumatoid arthritis (RA) means chronic inflammatory sickness with systemic characteristics involving joints, leading to erosive synovitis, degradation of cartilage, and destruction of joints. The aim of this study was for assessment of serum levels of B Cell Receptor (BCR) clones and Adiponectin (ADP) in RA and the correlation between them in biological, chemotherapy, biological, and chemotherapeutic treatment strategies. Seventy eight individuals have included in this study, 60 patients (51 females and 9 males) with 18 control (13 female and 5 male). Patients with RA were diagnosed by a consultant rheumatologist according to ACR / EULAR criteria in 2010. They were divided into three groups; patients had biological treatment (bio.), chemotherapy (chem.), and biological and chemotherapy. Evaluation of the RA activity using Disease Activity Score 28 (DAS28) was done. Enzyme-linked immunosorbent assay (ELISA) was used to detect B Cell Receptor and Adiponectin. BCR clones, ADP were assessed. The results showed a highly significant increase (p= 0.0001) in the serum level of BCR observed in both biological group and biological and chemotherapy groups as compared to control. The ADP serum level had a highly significant increase (p= 0.002) in the biological group as compared with the control group. There was a significant Negative correlation between ADP with BCR level (P-Value=0.039) in patients who had biological treatment. In conclusion, In patients who had biological treatment, there was a significant increase in serum BCR levels and ADP levels.